Isolation and characterization of four adenovirus type 12-transformed human embryo kidney cell lines. - Whittaker, J L (1984)
Four transformed cell lines were established from cultures of human embryo kidney (HEK) cells microinjected or transfected with cloned adenovirus 12 (Ad12) EcoRI-C DNA (0 through 16.5 map units of the left-hand end of the viral genome). Each cell line showed a different growth pattern. Southern blotting demonstrated that all of the cell lines contained Ad12-specific DNA sequences, but in the microinjected isolates these were at a much lower copy number than in the transfected isolate. Two cell lines (Ad12 HEK 1 and 3) appeared to contain tandemly repeated Ad12 EcoRI-C DNA fragments. Immunoprecipitation and Western blotting confirmed that Ad12 early region 1 (E1) proteins were being expressed by all four of the transformed cell lines, but indicated that E1A polypeptide expression was considerably less than E1B polypeptide expression. All of the Ad12-transformed HEK cell lines were tumorigenic when inoculated intracranially into athymic nude mice.